Answer:
Answer= A
Explanation:
equation (1) x=4y-94
equation (2) 3x+8y=218
step 1: for substitution method sub x in the second equation.
3(4y-94)+8y=218
step2: take rid of the bracket by multiplying it by 3.
12y-282+8y=218
(this is the initial expanding result which is answer A)
- The answer is not B or C because as they have both letters x and y the did not use substitution method, which will have a one letter result.
- The answer is not D because they did not multiply -94 by three when expanding the bracket.